2009
DOI: 10.1162/jocn.2009.21101
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities Affect Prefrontal Function in Children

Abstract: Abstract& Social inequalities have profound effects on the physical and mental health of children. Children from low socioeconomic status (SES) backgrounds perform below children from higher SES backgrounds on tests of intelligence and academic achievement, and recent findings indicate that low SES (LSES) children are impaired on behavioral measures of prefrontal function. However, the influence of socioeconomic disparity on direct measures of neural activity is unknown. Here, we provide electrophysiological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
187
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(213 citation statements)
references
References 48 publications
14
187
0
8
Order By: Relevance
“…One study found that low-income children exhibited lower prefrontal functioning compared to higherincome children. Specifically, the PFC functioning of low-income children in the study was similar to the level of functioning of individuals with damage to the PFC (Kishiyama et al 2009). In addition to effects on the developing brain, ACEs are related to poorer executive function and self-regulation, increased substance use, obesity, and risk-taking behaviors in adolescents and adults (see Table 1).…”
Section: Adverse Childhood Experiences and Cumulative Riskmentioning
confidence: 53%
“…One study found that low-income children exhibited lower prefrontal functioning compared to higherincome children. Specifically, the PFC functioning of low-income children in the study was similar to the level of functioning of individuals with damage to the PFC (Kishiyama et al 2009). In addition to effects on the developing brain, ACEs are related to poorer executive function and self-regulation, increased substance use, obesity, and risk-taking behaviors in adolescents and adults (see Table 1).…”
Section: Adverse Childhood Experiences and Cumulative Riskmentioning
confidence: 53%
“…Results from this line of work suggest income level disparities exist in cognitive processing related to working memory, language, incidental memory, and inhibition, again with lower income students not performing as well as their higher income counterparts [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 94%
“…Children 7-12 years old performed a target detection task designed to probe cognitive flexibility and working memory, which is related to lateral prefrontal cortex activation (Kishiyama et al 2009). Lower SES children showed reduced prefrontal cortex activation compared to children of high SES families, indicating delayed prefrontal cortex development and increased risks for delay in executive function.…”
Section: Brain: Functionmentioning
confidence: 99%